2019
DOI: 10.5812/jjcdc.95732
|View full text |Cite
|
Sign up to set email alerts
|

Cancers of Urinary System; Prevalence, Demographic

Abstract: Objectives: This investigation aimed to clarify the period prevalence (PP) and incidence rate (Irs) related to cancers of the urinary system in Isfahan province, Iran. Methods: Recorded data were obtained from the Isfahan Cancer Registry. The location of cancers was distinguished from the related established topography code (C64-C68). Period prevalence (PP) and Irs was identified per 100000 persons. Results: There were 2117 patients with urinary system cancers. The mean age ± SD was 63.6 ± 14.9 years old, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Bladder cancer had the highest prevalence (33.2%) and ureter the lowest (0.36%), among urinary cancers. Also, the mortality rate related to these cancers is at 11% during this period [14]. Due to the importance of urinary system cancers and the impact of prevention and early detection strategies on decreasing the burden of these malignancies, it is necessary to investigate these malignancies' incidence rates and epidemiological information to accomplish and create essential strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Bladder cancer had the highest prevalence (33.2%) and ureter the lowest (0.36%), among urinary cancers. Also, the mortality rate related to these cancers is at 11% during this period [14]. Due to the importance of urinary system cancers and the impact of prevention and early detection strategies on decreasing the burden of these malignancies, it is necessary to investigate these malignancies' incidence rates and epidemiological information to accomplish and create essential strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Kidney cancer is one of the 10 cancers with a high incidence rate among the southern Iranian population (17). Studies in Isfahan (Iran) reported the prevalence of kidney and ureteral cancers to be 8.1 and 0.4 per 100 00, respectively (18), and showed that urinary and kidney cancers had a rising trend of incidence, mortality, and prevalence in this region (19). In a study conducted in northern Iran, the standardized incidence of kidney and ureter cancer among women was 0.14 and 0.39, respectively (20).…”
Section: Introductionmentioning
confidence: 99%
“…2015), hastalık-tedavi yöntemi bazında maliyet analizi (Utaş, 2007;Gürsoy, 2008;Karaköse ve Yüksel, 2012;İrkilata ve ark. 2015;Eroymak ve Yiğit, 2017) (Öztürk, 2019); üriner sistem kanserleri yaygın görülmekte ve sağlık sistemine önemli bir maliyet ve yük getirmektedir (Ghamari, 2019). Kronik Böbrek Hastalığı dünyada salgın halinde görülmektedir (Bilgiç, 2020).…”
Section: Introductionunclassified